ANALISIS KEBIJAKAN MIGRANT PROTECTION PROTOCOL (MPP) PADA ERA DONALD TRUMP TAHUN 2019 - Upaningtyas, Putu Ditha Tilottami; Putri, Penny Kurnia; Parameswari, A.A.A Intan (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 2 No 1 (2022): Jurnal DIKSHI, 2022)
United States of America is a superpower country known as the nation of immigrants. Under Donald Trump’s administration, immigrants, asylum seekers, and refugees were considered an existential threat to the national security. Thus, Trump issued a policy to protect his country. The focus of this research is to find out why the US implemented the Migrant Protection Protocol (MPP) Policy under Donald Trump’s era in 2019. The scientific framework used in this research are Populism Perspective, Securitization Concept, and Realist Foreign Policy. The analysis that has been carried out by the author finds that the reasons for Trump's implementation of the MPP, are the illegal immigrant crisis, domestic-based crime, and eliminating jobs for local residents. As a populist actor, the arrival of immigrants, asylum seekers, and refugees are depicted as a threat to the security of the American people, which is why a firm policy is needed.